Lipedema: Clinical Features, Diagnosis, and Management - Mortada, Hatan; Alhithlool, Abdulmalek W.; AlBattal, Nouf Z.; Shetty, Rashika K.; AL-Mekhlafi, Ghaleb A.; Hong, Joon Pio; Alshomer, Feras (Archives of Plastic Surgery, 2025)
Lipedema is an adipose tissue disorder that principally affects women and is frequently misidentified as obesity or lymphedema. There have been relatively few studies that have precisely defined the pathogenesis, epidemiology, and treatment approaches for lipedema. However, successfully recognizing lipedema as a distinct condition is important for proper management. This review aimed to examine the existing literature on the epidemiology, pathogenesis, clinical presentation, differential diagnosis, and treatments for lipedema. The current research indicates that lipedema appears to be a clinical entity related to genetic factors and fat distribution, although distinct from lymphedema and obesity. Some available treatments include complex decongestive physiotherapy, liposuction, and laser-assisted lipolysis. The management of lipedema is complex and differs from that of lymphedema. Further high-quality randomized controlled trials are urgently needed to continue advancing our understanding of this often neglected disease and exploring optimal medical and surgical treatment regimens tailored specifically for lipedema patients. In summary, despite frequent misdiagnosis, enhanced recognition, and research into customized therapeutic strategies for this poorly characterized but likely underdiagnosed disorder represent promising steps forward.Level of evidence N/A.
Keywords: lipedema; lymphedema; liposuction